Habemus Papam: eleição papal nas coberturas midiáticas de jornais paulistas de Leão XIII (1878) a Francisco (2013) - Santos, Rafael Alberto Alves dos (2018)
"Which simulacrum of Pope does the Paulista press media build when showing us the leaders of the Roman Catholic Apostolic Church after its respective elections?" That problematic guides the present dissertation. Using a corpus from "O Estado de S. Paulo" newspaper pages and the "Folha de São Paulo" in a 135 period of years, it is possible to analyze how this media plans a typology confronting its own values with the ones from the Catholic Church, which shows the thematic role of the Pope. The hypothesis is that the newspaper shows ways of presence for each Pope according to their own interests, trying to deceive the image of the elected Cardinal. Still, in a new perspective of the new theory that despite the restrictions of the Church, the simulacrum carries a way of being in the World deceived by individual characteristics from each Cardinal that is elected - in a syncretism of destinators. This investigation aims to deepen the reflection about language syncretism in the truths of the analyzed pages. On one hand, the Church as a destinator schedules the thematic route for the Popes. This route is lived by one Cardinal, himself as a destinator. In the Saint Peter Basilica balcony, these routes unify themselves and are projected for the World. Captured by the media, the scene is reorganized in another way through the newspaper pages by the language syncretism - verbal, visual and spacial. The theoretical foundation is the Discursive Semiotic, created by Algirdas Greimas and its unfolding in the Social Semiotics by Eric Landowski. It is taken to consideration the Plastic Semiotic, organized by Jean Marie Floch and build on by Ana Claudia Oliveira, especially in the studies of esthesia that make us feel the new Pope. The results aim to the possibility of a link between the simulacrum typologies built by the medias with interaction and risks, showing in the media projection the Catholic leaders and that there is a predominance in the hazards of accidents that reveals a dynamic by visibility. The new is, in fact, a figurativization of the new that remains in its depths with the intentionality and propagations of the Church's old speech